2013
DOI: 10.1111/arcm.12054
|View full text |Cite
|
Sign up to set email alerts
|

Flax look‐alikes: Pitfalls of ancient plant fibre identification

Abstract: Plant fibres have been used since ancient times in numerous applications ranging from nets and basketry to textiles for clothing. A proper identification of plant fibre remains in archaeological excavations provides important information about resource exploitation and agriculture. In order to identify plant fibres, a series of fibre features-cross-section diameter, lumen diameter, dislocations (nodes), cross markings, cross-section shape and lumen shape-have been defined and characteristic traits of these fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…This study has demonstrated that fibre cells from the inner bark of New Zealand species thought to be used for tapa‐making can be successfully distinguished from those found in the inner bark of Pacific plant species known to be used for tapa‐making using PLM, provided a range of both morphological and optical features of the cells are observed and compared. Indeed, the importance of observing a range of fibre cell features when attempting to identify species has been highlighted by others (Haugan and Holst 2014; Paterson et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has demonstrated that fibre cells from the inner bark of New Zealand species thought to be used for tapa‐making can be successfully distinguished from those found in the inner bark of Pacific plant species known to be used for tapa‐making using PLM, provided a range of both morphological and optical features of the cells are observed and compared. Indeed, the importance of observing a range of fibre cell features when attempting to identify species has been highlighted by others (Haugan and Holst 2014; Paterson et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has highlighted PLM for distinguishing among plants between and within genera accurately. PLM allows the identification and enhancement of morphological and optical properties (Bergfjord and Holst 2010; Haugan and Holst 2013, 2014; Lukesova 2017; Paterson et al . 2017; Lukešová et al .…”
Section: Introductionmentioning
confidence: 99%
“…Bast fibres from different species are difficult to identify and so a careful investigation is necessary to ensure correct identification (Bergfjord et al . ; Haugan and Holst ). In this paper, we present an experimental study of modern hop fibres using standard, white light and polarization microscopy—the modified Herzog test (Herzog , ; Petraco and Kubic ; Haugan and Holst ) and microchemical tests (Luniak ; Stratmann ; Wülfert ).…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, there has been an increased interest in the scientific identification of archaeological and historical plant fibre material (see, e.g., Bergfjord et al . ; Haugan and Holst , ; Skoglund et al . ; Lukešová ; Lukešová et al .…”
Section: Introductionmentioning
confidence: 99%
“…medulla shape and size, cuticular scale pattern, Tridico 2009) often facilitate, if present, the identification of animal fibres from artefacts, although processing and ageing can limit identification to higher taxonomic levels (Tridico et al 2014). Processing and age of plant materials can likewise pose ongoing challenges for textile scientists, archaeologists, conservators and museums professionals, since processing of plant material for textile production frequently obscures macroscopic diagnostic features (Jakes et al 1994), and even microscopic features of different plant species can appear remarkably similar (Bergfjord et al 2010;Haugan and Holst 2014).…”
Section: Introductionmentioning
confidence: 99%